Spin pair geometry revealed by high-field DEER in the presence of conformational distributions - Polyhach, Ye; Godt, A.; Bauer, C.; Jeschke, G. (Journal of magnetic resonance (1997), 2007)
Orientation selection on two nitroxide-labelled shape-persistent molecules is demonstrated by high-field pulsed electron–electron double resonance experiments at a frequency of 95 GHz with a commercial spectrometer. The experiments are performed with fixed observer and pump frequencies by variation of the magnetic field, so that the variation of both the dipolar frequencies and the modulation depths can be analyzed. By applying the deadtime-free four-pulse double electron–electron resonance (DEER) sequence, the lineshapes of the dipolar spectra are obtained. In the investigated linear biradical and equilateral triradical the nitroxide labels undergo restricted dynamics, so that their relative orientations are not fixed, but are correlated to some extent. In this situation, the general dependence of the dipolar spectra on the observer field can be satisfyingly modelled by simple geometrical models that involve only one rotational degree of freedom for the biradical and two rotational degrees of freedom for the triradical. A somewhat better agreement of the dipolar lineshapes for the biradical is obtained by simulations based on a molecular dynamics trajectory. For the triradical, small but significant deviations of the lineshape are observed with both models, indicating that the technique can reveal deficiencies in modelling of the conformational ensemble of a macromolecule.